Work-related gender differences in physician-certified sick leave: a prospective study of the general working population in Norway - Tom Sterud (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: This study aimed to examine gender differences in physician-certified sick leave and the extent to which these differences can be explained by work-related psychosocial and mechanical risk factors. METHODS: Randomly drawn from the general population in Norway, the cohort comprised working men and women aged 18-69 years (N=12 255, response rate at baseline = 60.9%). Eligible respondents were interviewed in 2009 and registered with an active employee relationship of ≥100 actual working days in 2009 and 2010 (N=3688 men and 3070 women). The study measured 11 work-related psychosocial factors and 11 mechanical exposures, and outcomes of interest were physician-certified general sick leave (GSL) >0 days and long-term sick leave (LTSL) ≥40 working days during 2010. RESULTS: Women reported a significantly higher level of exposure to 9 of the 11 psychosocial factors evaluated. For mechanical factors, the reporting was mixed. After controlling for age, educational level, sick leave during 2009, housework, working hours and family status, a 1.7-fold risk for GSL and LTSL were found among women. In comparison with the initial model, adjusting for psychosocial factors reduced the excess risk by 21% and 27% for GSL and LTSL, respectively. The total effect of mechanical factors was negligible. Differences between occupations held by women and men explained an additional one-tenth of the excess risk for LTSL among women. CONCLUSIONS: Work-related psychosocial factors contributed significantly to a higher level of GSL and LTSL among women. The most important factors were demands for hiding emotions, emotional demands, and effort-payment imbalance.